Saúde vocal e docência no ensino superior - Braga Júnior, Francisco Varder (2013)
This study aimed to investigate the relationship between vocal health and teaching in higher education, the influence of conditioning factors to vocal health on the performance of professors at the Federal Rural University of the Semi-arid, and to investigate these professionals perceptions, vocal complaints and workplace. The sample was composed of more than 50% of the headcount in the four university campuses, with a total of 236 professors surveyed. The campuses in Angicos, Caraúbas, Pau dos Ferros, and Mossoró are all located in the state of Rio Grande do Norte. Questionnaires were used as instruments to collect data. There were objective and semi-structured questions that were requested to the professors to obtain the following data: identification data, professional data, conditioning factors and symptoms of vocal health (vocal habits, environmental conditions and classroom habits related to food and hydration). By crossing the variables, we verified the existence of an association between vocal symptoms and variables related to general health symptoms, identification data and professionals, as well as voice change after start teaching with inappropriate classroom conditions. The most frequent vocal symptoms are: hoarseness, rasping throat sensation, sore throat, hoarseness, and failing voice. In contrast, general health symptoms presented as follows: stress, anxiety, rhinitis, spine problems and gastric problems. As for the workplace, this proved indifferent as the reading of the proposed scale and the vocal habits, to food and hydration mostly also set up as adequate. Therefore, this study allowed us to demonstrate the main difficulties of professors at Federal Rural University of the Semi-arid with respect to vocal health and teaching, providing a reflection and contribution with other existing studies at literature, serving as a guide for future work in this Institution, and to suggest measures aimed at occupational health, specifically for professors vocal health of higher education.